Blank canvas or under construction? Examining the pre-academy experiences of young developing professional team sports athletes - Papastaikoudis, Foivos; Collins, Rosie; Collins, Dave (Frontiers in Sports and Active Living, 2023)
Extensive research has been carried out on Talent Development (TD) environments and an increasing amount of work shows the development of psychological characteristics as an important formal part of the academy experience. Importantly, however, very little attention has been paid to what types of skills, if any, young players arrive with. In other words, there seems to be an assumption that young athletes arrive at the academy as a blank canvas. To investigate this, we looked across a sample of young footballers’ and rugby players’ experiences prior joining the academy. Individual semi-structured interviews were conducted, and data were analysed via thematic analysis. Our findings suggested that young athletes acquired an aptitude from general experiences, which they then translated into more specific skills to meet particular challenges before they arrived at the academy. Implications include the need for coaches and psychologists to assess young athletes’ skillsets and pre-academy experiences upon arrival and use this as a starting point for developing tailored and individualised pathways that would enable them maximise their potential.